1968
DOI: 10.1037/h0025905
|View full text |Cite
|
Sign up to set email alerts
|

Some determinants of gratitude.

Abstract: It was predicted that feelings of gratitude are a function of the recipient's perceptions of the intention of the benefactor, the cost to the benefactor in providing the benefit, and the value of the benefit. 126 male undergraduates read variants of each of 3 story themes and indicated their perceptions of the above 3 independent variables and also how grateful they felt toward the benefactor. Each of the three predicted factors was found to be significantly related to felt gratitude. No interactions were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
231
4
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(255 citation statements)
references
References 6 publications
15
231
4
5
Order By: Relevance
“…Overall then, program value is a determinant of gratitude. Motives also strongly determine channel partner gratitude, providing support for theorizing in early gratitude literature (Tesser et al 1968). Unlike research that regards motives on a continuum, from benevolent to ulterior (e.g., Tsang 2006), we demonstrate that partner program members actually perceive motives in a more nuanced way.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Overall then, program value is a determinant of gratitude. Motives also strongly determine channel partner gratitude, providing support for theorizing in early gratitude literature (Tesser et al 1968). Unlike research that regards motives on a continuum, from benevolent to ulterior (e.g., Tsang 2006), we demonstrate that partner program members actually perceive motives in a more nuanced way.…”
Section: Discussionmentioning
confidence: 71%
“…For example, a costly favor elicits stronger feelings of gratitude than a less costly one in experimental studies (Lane and Anderson 1976;Tesser et al 1968). Building on sociology research, Palmatier et al (2009) show that relationship investments lead to more gratitude in business-to-business settings.…”
Section: Antecedents Of Gratitude and Indebtednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prediction was supported: Perceived responsiveness predicted feelings of gratitude, B = .46, p < .001, d = 0.79. & Collins, 1988) and conceptually replicate findings linking value of benefit to gratitude (Tesser et al, 1968). To test the robustness of perceived responsiveness as a predictor, we included all three primary predictors of gratitude-surprisingness of event, liking for the benefit, and thoughtfulness of the benefactor-in the model simultaneously.…”
mentioning
confidence: 89%
“…In this study, we explored aspects of gratitude that lie beyond reciprocity. We suggest that gratitude promotes relationship formation and maintenance.Previous research has suggested that the main ingredients of gratitude are an intentional gesture that is of value to the recipient (Lane & Anderson, 1976;Tesser, Gatewood, & Driver, 1968;Weiner, Russell, & Lerman, 1978, 1979 and costly to the benefactor (Okamoto & Robinson, 1997;Tesser et al, 1968). Given that benefits bring information about the relationship motivations of the benefactor (Ames, Flynn, & Weber, 2004), we suggest an additional critical appraisal for the emotion of gratitude that is interpersonal in nature: perceived responsiveness to the self (Reis, Clark, & Holmes, 2004 (Schwarz & Clore, 2007) in line with emotionrelevant appraisals (Lerner & Tiedens, 2006), then considering the relational implications of gratitude is essential for understanding its role in social life.…”
mentioning
confidence: 99%